Perbedaan Recovery Denyut Nadi Berdasarkan Jeda Waktu Makan Setelah Olahraga - Wati, Isti Dwi Puspita (STAMINA, 2023)
The right time to eat for athletes is suggested to support achievement. However, research evidence on this matter still needs to be more extensive. This study aims to reveal evidence of differences in pulse after exercise by looking at the pause after eating. A one-shot case study experiment was conducted with 22 student samples divided into three groups. The first group of 7 people exercised immediately after eating (A), the second group of 8 people 1 hour after eating (B), and group 3 2 hours after eating (C). Pulse testing is carried out before exercising (basketball man to man half court) for 10 minutes, and then the pulse is measured after playing; further measurements are carried out every 3 minutes up to 4 times and 1 hour after stopping playing. The rest is done passively. The instruments used are tests and measurements of the pulse. Data analysis used is descriptive statistics and different tests using ANOVA. The results showed that, in this case, group A and Group C had the same pulse rate of 65 per minute, while Group B had an average of 77.5 per minute. Pulse after exercising consecutively 1130.29, 128, and 128.9 per minute. At the end of measuring the pulse after 1 hour of rest, it turned out that group C had the lowest pulse compared to groups A and B. Keywords: Recovery, Food before sport, pulse